Answer:
y+2=m(x+2)
Step-by-step explanation:
y - y1 = m(x - x1)
y- (-1) = m( x-(-1) )
y+2 = mx +2m
Answer:
The tabulated value is less than the calculated value, therefore we accept the null hypothesis and It show that there is a difference in the mean overall distance of brands.
Step-by-step explanation:
6/10
300/500
30/50
60/100
12/20
Answer:
i=7
Step-by-step explanation:
9514 1404 393
Answer:
Step-by-step explanation:
The first term is 2, so part of the recursive definition is ...
f(1) = 2
The common ratio is 6/2 = 3, so each term is 3 times the previous one. That part of the recursive definition is ...
f(n) = 3·f(n -1)
These two parts of the definition match choice C.